Performance evaluation of rejuvenated recycled asphalt blends at high and intermediate pavement temperatures. Issue 12 (15th October 2022) - Ansari, Mohd Tahir; Khatri, Khailesh; Vishnu, R.; Chowdary, Venkaiah
ABSTRACT: Blending charts are widely used in the design of recycled asphalt mixes. The amount of recycled binder in the total blend (R/T) can be enhanced by the addition of rejuvenator. The present study investigated two methods of blending approaches. In approach 1, different levels of rejuvenator were added to the recycled binder and R/T was determined for a selected virgin and target binder grade. Approach 2 consisted in determining the rejuvenator content for a selected R/T and virgin binder grade. Nine different binder blends targeted for the same viscosity were synthesised using the two approaches. Blends synthesised using approach 2 accommodated higher R/T. Rutting and oxidative ageing potential of the binder blends was investigated using MSCR experiment and Glower–Rowe's (G–R) parameter respectively. Blends synthesised using approach 2 exhibited higher non-recoverable creep compliance, poor recovery characteristics and high-stress sensitivity. The rejuvenated recycled asphalt blends endured longer ageing hours before reaching the threshold levels of crack initiation expressed using the G–R parameter. Even though the blending approach 1 incorporated lower levels of RAP than approach 2, from the performance space diagram, it can be found that blends had almost equal rutting and ageing resistance with the target binder grade.